A review on energy efficiency standards and labels: present status and implementation possibilities in malaysia - T.M.I. Mahlia,; H.H. Masjuki,; I.A. Choudhury; and R. Saidur R. Saidur (ASEAN Journal on Science and Technology for Development, 2001)
This article is a review on energy efficiency standards  and labels for household electrical appliances around the world. Through the review of other country experiences on energy efficiency standards and labels, we attempt to identify savings possibilities in Malaysian households. The implementation possibilities of standards and labels for various household electrical appliances in Malaysia are also examined. It is found that various household appliances in Malaysia offer some potential in reducing electricity consumption. Finally, it is concluded that there are many advantages for Malaysia to implement the standards and labels for household electrical appliances as soon as possible in order to reduce electricity  bills  and energy  consumption  in Malaysian  households.